2023
DOI: 10.48550/arxiv.2301.00892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bias Correction of Operational Storm Surge Forecasts Using Neural Networks

Abstract: Storm surges can give rise to extreme floods in coastal areas. The Norwegian Meteorological Institute (MET Norway) produces 120-hour regional operational storm surge forecasts along the coast of Norway based on the Regional Ocean Modeling System (ROMS), using a model setup called Nordic4-SS. Despite advances in the development of models and computational capabilities, forecast errors remain large enough to impact response measures and issued alerts, in particular, during the strongest storm events. Reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A summary of the studies using ANN before 2020 can be found in Al Kajbaf and Bensi [19]. In recent years, ANNs have continued to be applied in storm surge problems [10,19,44,57,90,91,[120][121][122][123] and are also used in combination with CNN to extract feature representation from spatial data [78,124]. However, ANNs also have some limitations, especially in time series prediction.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the studies using ANN before 2020 can be found in Al Kajbaf and Bensi [19]. In recent years, ANNs have continued to be applied in storm surge problems [10,19,44,57,90,91,[120][121][122][123] and are also used in combination with CNN to extract feature representation from spatial data [78,124]. However, ANNs also have some limitations, especially in time series prediction.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Tayel and Oumeraci [137] developed a NARX neural network for nonlinearly correcting the numerical forecast results of storm tides. Tedesco et al [121] demonstrated that the forecasts of the Regional Ocean Modeling System (ROMS) can be improved with residual learning by testing a simple error mapping technique and a more sophisticated neural network. These studies show that ML-aided post-processing is a promising direction that can not only enhance the efficiency and accuracy of numerical models but also reduce computational demands.…”
Section: Ml-based Post-processingmentioning
confidence: 99%